2012
DOI: 10.1097/ta.0b013e318256a150
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors influencing bone graft infection after cranioplasty

Abstract: Prognostic/therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
56
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 13 publications
10
56
1
Order By: Relevance
“…Although autografting, that is, either reimplantation of the excised bone flap [6,7], or transfer of cortical, cancellous or corticocancellous bone from any anatomic site to the defect site in the same subject, is obviously the best choice owing to the lack of immune or foreign body reactions, absence of a risk of transmission of disease, and the potential of the graft to be incorporated as biologically active and dynamic living tissue it has certain inherent limitations and disadvantages. Bone flap/graft resorption and infection [8,9], donor site morbidity, inadequate quantity of graft harvestable to bridge large cranial defects, prolonged intra-operative time, intraoperative blood loss and requirement of transfusions, need for surgical expertise and delayed post operative recovery [10] are definite drawbacks of autografting. Advanced age, presence of comorbidities, poor general condition of the patient, difficulties with bone flap storage, acute case scenarios and anatomical constraints can lead to difficulty in autografting or to the loss of the excised bone flap in a large number of cases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although autografting, that is, either reimplantation of the excised bone flap [6,7], or transfer of cortical, cancellous or corticocancellous bone from any anatomic site to the defect site in the same subject, is obviously the best choice owing to the lack of immune or foreign body reactions, absence of a risk of transmission of disease, and the potential of the graft to be incorporated as biologically active and dynamic living tissue it has certain inherent limitations and disadvantages. Bone flap/graft resorption and infection [8,9], donor site morbidity, inadequate quantity of graft harvestable to bridge large cranial defects, prolonged intra-operative time, intraoperative blood loss and requirement of transfusions, need for surgical expertise and delayed post operative recovery [10] are definite drawbacks of autografting. Advanced age, presence of comorbidities, poor general condition of the patient, difficulties with bone flap storage, acute case scenarios and anatomical constraints can lead to difficulty in autografting or to the loss of the excised bone flap in a large number of cases [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…17,38,42,48 Finally, recent studies, including a meta-analysis, have shown no difference in complication rates between early and late cranioplasties. 5,24,39,51 We did not account for the timing of cranioplasty in our study because our patients underwent early operation unless there was a convincing need to delay it, such as the presence of wound dehiscence, hydrocephalus, or evidence of persistent brain swelling. We balanced the wait for maximal neurological improvement with early intervention to prevent hemodynamic changes in the CSF and cerebral blood flow that may occur if the flap was left out for a prolonged period of time.…”
Section: Timing Infection and Hydrocephalusmentioning
confidence: 99%
“…‱ Increased Surgical Time [6,10,11] The literature suggests that increased surgical time dramatically increases the risk of infection. Longer surgical times (greater than 4 h) were associated with a higher risk of infection.…”
Section: Discussionmentioning
confidence: 99%